Personaje animado para la Universidad Nacional de Chimborazo como estrategia comunicacional para medios digitales. - Centeno Colcha, Katheryn Elizabeth (2025)
The research focused on the development of an animated character as a communication strategy for the digital media of the Universidad Nacional de Chimborazo, using a qualitative methodology with exploratory and descriptive approaches under a non-experimental transversal design. The research process integrated various methods such as analytical synthetic, empirical, phenomenological and design, supported by multiple data collection techniques including bibliographic research, brainstorming using the lotus flower technique to define the character's personality, focus groups to evaluate the quality of the animation and its perception, direct observation of the communication behavior of the university community, and interviews to identify specific needs. The qualitative data were analyzed using Atlas Ti, allowing the development of a proposal based on Bryan Tillman's character creation methodology, which includes the multidimensionality matrix. The design process followed a technical sequence that ranged from initial sketching to final animation, including 2D digitization. To start 3D modeling, primitives are applied, then sculpting, texturing, angering and rigging are carried out. The final result was an animated character that effectively incorporated the identifying elements of the university, becoming a coherent and strategic communication tool for the institution